Molecular and neural adaptations to neuromuscular electrical stimulation; Implications for ageing muscle. (January 2021) - Guo, Yuxiao; E Phillips, Bethan; Atherton, Philip J; Piasecki, Mathew
Highlights: Muscle atrophy and functional declines observed with advancing age can be minimized via various NMES protocols. Animal models have shown that NMES induces motor axon regeneration and promotes axonal outgrowth and fibre reinnervation. The activation of BDNF-trkB contributes to promotion of nerve growth and survival and mediates neuroplasticity. NMES is able to regulate muscle protein homeostasis and elevate oxidative enzyme activity. Abstract: One of the most notable effects of ageing is an accelerated decline of skeletal muscle mass and function, resulting in various undesirable outcomes such as falls, frailty, and all-cause mortality. The loss of muscle mass directly leads to functional deficits and can be explained by the combined effects of individual fibre atrophy and fibre loss. The gradual degradation of fibre atrophy is attributed to impaired muscle protein homeostasis, while muscle fibre loss is a result of denervation and motor unit (MU) remodelling. Neuromuscular electrical stimulation (NMES), a substitute for voluntary contractions, has been applied to reduce muscle mass and functional declines. However, the measurement of the effectiveness of NMES in terms of its mechanism of action on the peripheral motor nervous system and neuromuscular junction, and multiple molecular adaptations at the single fibre level is not well described. NMES mediates neuroplasticity and upregulates a number of neurotropic factors, manifested by increased axonal sprouting and newly formed neuromuscular junctions. Repeated involuntary contractions increase the activity levels of oxidative enzymes, increase fibre capillarisation and can influence fibre type conversion. Additionally, following NMES muscle protein synthesis is increased as well as functional capacity. This review will detail the neural, molecular, metabolic and functional adaptations to NMES in human and animal studies.